School gardens to promote food and nutrition security: Insights from Sri Lankan school educators - Karunanayaka, M.M.S.; Indramali, O.S.; Perera, T.; Mohotti, J.; Hunter, D.; Silva, K.D.R.R. (2024)
Integrating school gardens into educational setting is a promising strategy for improving food and nutrition security in schools. Understanding the potential benefits and challenges associated with gardening is essential for the successful implementation and maintenance of school garden programs. Therefore, this study aimed to explore the potential of school gardens to enhance food and nutrition security within Sri Lankan schools by gathering insights from educators engaged in school garden-based programs. Data were collected through in-depth interviews with 22 educators who teach food-related subjects across 18 secondary schools in two districts in Sri Lanka. Thematic analysis was conducted using NVivo software to analyze the themes emerged. Many educators reported that school garden-based initiatives could enhance students' access to nutritious food, increase the availability of nutritious food crops within the school premises and foster community involvement. Some participants highlighted the benefits of combining nutrition education with gardening, which promotes healthy eating habits among students. The use of garden harvest to supplement school meal programs and promote healthier food choices in school canteens was also emphasized. However, challenges such as limited time allocation for garden work, insufficient garden resources, lack of technical assistance and difficulties in maintaining gardens during school holidays hinder the full potential of these programs. The study concluded that school gardens can contribute positively to the nutritional well-being of students. To fully leverage the benefits of school gardens in promoting food and nutrition, future research and policy efforts should focus on scaling up successful models while mitigating existing barriers.